Physics, asked by laxmipargai2, 5 months ago

Class 9 motion all formulas​

Answers

Answered by sunil1122
1

Explanation:

Motion

Equation of Motion:

Relation among velocity, distance, time and acceleration is called equations of motion. There are three equations of motion:

First Equation of Motion:

The final velocity (v) of a moving object with uniform acceleration (a) after time, t.

Let, the initial velocity = u.

Final velocity = v.

Time = t

Acceleration = a

We know that, Acceleration (a)

=

Change in velocity

Time taken

a

=

Final velocity-Initial velocity

Time taken

a

=

v

u

t

a

t

=

v

u

a

t

v

=

u

v

=

u

a

t

v

=

u

+

a

t

---(i)

This equation is known as first equation of motion.

Second Equation of Motion:

Distance covered in time (t) by a moving body.

Let, Initial velocity of the object = u

Final velocity of the object = v

Acceleration = a

Time = t

Distance covered in given time = s

We know that,

Average velocity

=

Initial velocity+Final velocity

2

∴ Average velocity

=

u

+

v

2

----(ii)

We know that, Distance covered (s) in given time = Average velocity x Time

Or, s = Average velocity x Time -----------------(iii)

After substituting the value of average velocity from equation (ii) we get

s

=

u

+

v

2

×

t

After substituting the value of ‘v’ from first equation of motion we get,

s

=

u

+

(

u

+

a

t

)

2

×

t

s

=

u

+

u

+

a

t

2

×

t

s

=

2

u

+

a

t

2

×

t

s

=

2

u

t

+

a

t

2

2

s

=

2

u

t

2

+

a

t

2

2

s

=

u

t

+

a

t

2

2

s

=

u

t

+

1

2

a

t

2

----(iv)

The above equation is known as Second equation of motion.

Third Equation of Motion:

The third equation of motion is derived by substituting the value of time (t) from first equation of motion.

We know from first equation of motion,

v

=

u

+

a

t

v

u

=

a

t

a

t

=

v

u

t

=

v

u

a

-----(v)

We know that the second equation of motion is,

s

=

u

t

+

1

2

a

t

2

By substituting the value of

t

from euqation (v) we get

s

=

u

(

v

u

a

)

+

1

2

a

(

v

u

a

)

2

s

=

u

×

v

u

a

+

1

2

a

(

v

u

)

2

a

2

s

=

u

(

v

u

)

a

+

a

×

(

v

u

)

2

2

×

a

×

a

s

=

u

v

u

2

a

+

(

v

u

)

2

2

a

s

=

2

(

u

v

u

2

)

+

(

v

u

)

2

2

a

2

a

s

=

2

u

v

2

u

2

+

v

2

+

u

2

2

u

v

2

a

s

=

2

u

2

+

v

2

+

u

2

2

a

s

=

u

2

+

v

2

2

a

s

+

u

2

=

v

2

v

2

=

u

2

+

2

a

s

---(vi)

This is called the Third equation of motion.

Answered by createnshine
0

Answer:

there in tb

Explanation:                                                                        yes

Similar questions